Retinal Inflammation, Oxidative Stress, and Vascular Impairment Is Ablated in Diabetic Mice Receiving XMD8-92 Treatment - Howell, Scott J.; Lee, Chieh A.; Batoki, Julia C.; Zapadka, Thomas E.; Lindstrom, Sarah I.; Taylor, Brooklyn E.; Taylor, Patricia R. (Frontiers in Pharmacology, 2021)
The global number of diabetics continues to rise annually. As diabetes progresses, almost all of Type I and more than half of Type II diabetics develop diabetic retinopathy. Diabetic retinopathy is a microvascular disease of the retina, and is the leading cause of blindness in the working-age population worldwide. With such a significant health impact, new drugs are required to halt the blinding threat posed by this visual disorder. The cause of diabetic retinopathy is multifactorial, and an optimal therapeutic would halt inflammation, cease photoreceptor cell dysfunction, and ablate vascular impairment. XMD8-92 is a small molecule inhibitor that blocks ERK5 (extracellular signal-related kinase 5) and BRD4 (bromodomain 4) activity. ERK5 elicits inflammation, is increased in Type II diabetics, and plays a pathologic role in diabetic nephropathy, while BRD4 induces retinal inflammation and plays a role in retinal degeneration. Taken together, we hypothesized that XMD8-92 would be a good therapeutic candidate for diabetic retinopathy, and tested XMD8-92 in a murine model of diabetic retinopathy. In the current study, we developed an in vivo treatment regimen by administering one 100ul intraperitoneal injection of saline containing 20uM of XMD8-92 weekly, to streptozotocin (STZ)-induced diabetic mice. XMD8-92 treatments significantly decreased diabetes-mediated retinal inflammation, VEGF production, and oxidative stress. Further, XMD8-92 halted the degradation of ZO-1 (zonula occludens-1), which is a tight junction protein associated with vascular permeability in the retina. Finally, XMD8-92 treatment ablated diabetes-mediated vascular leakage and capillary degeneration, which are the clinical hallmarks of non-proliferative diabetic retinopathy. Taken together, this study provides strong evidence that XMD8-92 could be a potentially novel therapeutic for diabetic retinopathy.